The synoptic variability of thermospheric and mesospheric winds observed using a Fabry-Perot interferometer - Aruliah, Anasuya Lohini (UCL (University College London), 1992)
Thermospheric neutral winds have been routinely observed in Northern Scandinavia since 1981 using ground-based Fabry-Perot Interferometers (FPI) to measure the Doppler shifts of the atomic oxygen emission at 6300Å. Data have been collected each winter period between August and April. The database from Kiruna (67.8°N, 20.4°E), consisting of nine successive winters of observations, has been used to study the long-term behaviour of thermospheric neutral winds at high-latitudes in response to changes in the solar cycle, season and geomagnetic activity. Three significant characteristics were noticed. First, both the seasonal and geomagnetic response of the neutrad winds showed a solar cycle variation which appears to be solely a high-latitude phenomenon. Second, the seasonal analysis showed a significant asymmetry between the spring and autumn equinox periods. This is attributed mainly to an equinoctial asymmetry in the coupling between the solar wind and the magnetosphere and consequently to the high-latitude ionospheric convection. Third, the difference in the neutral wind response for solar maximum and minimum indicates that the Kp index is not a sufficient and unique indicator of the magnetospheric excitation of the thermosphere. Two smaller Scandinavian databases exist, from Kilpisjarvi (69.1°N, 20.8°E) and Svalbard (78.2°N, 15.6°E). Case studies have been compiled for the winter of 1987-1988 using neutral wind vectors obtained simultaneously from all three auroral sites. The results have been compared with the UCL-Sheffield three-dimensional, time-dependent global model of the thermosphere/ionosphere. Simultaneous data from three sites impose more stringent bounds for comparison with the model. Incorporation of a state-of-the-art Gallium Arsenide imaging detector into the FPI has made possible observation of the weak, infra-red emission line of the hydroxyl transition at 8430Å and thereby achieved continuous monitoring of the upper mesosphere. A strong semidiurnal variation and signatures of gravity waves were ...